Osteoporosis medication dispensing for older Australian women from 2002 to 2010: influences of publications, guidelines, marketing activities and policy1. (30th August 2014) - Peeters, Geeske; Tett, Susan E.; Duncan, Emma L.; Mishra, Gita D.; Dobson, Annette J.
ABSTRACT Purpose Developments in anti‐osteoporosis medications (AOMs) have led to changes in guidelines and policy, which, along with media and marketing strategies, have had an impact upon the prescribing of AOM. The aim was to examine patterns of AOM dispensing in older women (aged 76–81 years at baseline) from 2002 to 2010. Methods Administrative claims data were used to describe AOM dispensing in 4649 participants (born in 1921–1926 and still alive in 2011) in the Australian Longitudinal Study on Women's Health. The patterns were interpreted in the context of changes in guidelines, indications for subsidy, publications (scholarly and general media), and marketing activities. Results Total use of AOM increased from 134 DDD/1000/day in 2002 to 216 DDD/1000/day in 2007 but then decreased to 184 DDD/1000/day in 2010. Alendronate was the most commonly dispensed AOM but decreased from 2007, while use of risedronate (2002 onward), strontium ranelate (2007 onward) and zoledronic acid (2008 onward) increased. Etidronate and hormone replacement therapy (HRT) prescriptions gradually decreased over time. The decline in alendronate dispensing coincided with increases of other bisphosphonates and publicity about potential adverse effects of bisphosphonates, despite relaxing indications for bone density testing and subsidy for AOM. Conclusions Overall dispense of AOM from 2002 reached a peak in 2007 and thereafter declined despite increases in therapeutic options and improved subsidised access. The recent decline in overall AOM dispensing seems to be explained largely by negative publicity rather than specific changes in guidelines and policy. Copyright © 2014 John Wiley & Sons, Ltd.